Perpektif Kritis Kebijakan Pembaharuan Agraria Indonesia dari Rejim Orde Baru ke Rejim Reformasi - Sukardi Sukardi (Centre for Public Policy and Management Studies, 2004)
The agrarian problems in Indonesia have revealed the various gaps of resources occupation which has received inadequate atttention by the regimes throughout the time. The anaysis of agrarian reform history in Indonesia has expounded the sistemic state suppression toward the public. The characteristics and patterns of the existing agrarian policy have illustrated the resonance of many ideological struggles happening at the macro praxis level of development. The public struggle, manifested in various communal property right is fronted by the state who is highly productive in making hegemonic public policies in the social setting arena. The horizon of this struggle is characterized by a tug and war between the state center approch views and the society center approach views with some stream variants. Analysis has shown the different articulation values between the Old Order and new Order regimes. In the light of class analytic approach, the Old Order regime put more emphasis on a more populous agrarian policies based on neo-Marxist views. The New Order dominantly implement agrarian policies which are based on state center perspectives with the choice of state interest approach, strengtened by policies which take the side of liberal capitalist with growing systemic repression level. The Reform regime uses advocacy coalition framework approach for agrarian policy. The most important hypotetical implication of this analysis is if the state functions are not capable in becoming the articulator of public policy, the public itself will pursue collective policy which is known as land-reform by leverage.Kata kunci : state center approach, society center approach, land reform by leverage, agrarian reform, advocacy coalition